The effect of centrifugation at 1000 rpm on crude palm oil characteristics / Mohd Faisal Mohd Zaki - Mohd Zaki, Mohd Faisal (2010)
Today, almost all energy in the world is extracted from petroleum base. At current rate of usage the source of petroleum will meet it end sooner or later. Alternative energy is needed to replace the current source of energy. Alternative energy can come from various type of source such as plant, solar and etc. Crude palm oil (CPO) is renewable and is safe and easy to handle. CPO is one of the vegetable oil that can be used in diesel engine.. However, using CPO as fuel in diesel engine caused clogging in the fuel system. This study focused on finding out the effect of Centrifugation at 1000 rpm on CPO characteristic. The CPO was centrifuge and the liquid (olein) was collected in order to measure its characteristic in term of viscosity, density, energy content and flash point. Results show that kinematic viscosity of CPO reduced from 64.0593 mm2 /s to 43.065 mm2 /s. Density of centrifuged CPO slightly reduced from 862.2 kg/m3 to 833.2 kg/m3 while energy content remain the same at range of 39000 J/g to 40000 J/g. Flash point for centrifuged crude palm oil is 263°Celsius. At speed of 1000 rpm, percentage of separation between Olein and Stearin increase proportional to increment of temperature.